An Overview of Lung Cancer in Women and the Impact of Estrogen in Lung Carcinogenesis and Lung Cancer Treatment - Rodriguez-Lara, Vianey; Avila-Costa, Maria Rosa (Frontiers in Medicine, 2021)
Lung cancer incidence and mortality have significantly increased in women worldwide. Lung adenocarcinoma is the most common form of lung cancer globally. This type of lung cancer shows differences by sex, including the mutational burden, behavior, clinical characteristics, and response to treatment. The effect of sex on lung cancer patients’ survival is still controversial; however, lung adenocarcinoma is considered a different disease in women and men. Moreover, lung adenocarcinoma is strongly influenced by estrogen and is also different depending on the hormonal status of the patient. Young premenopausal women have been explored as an independent group. They presented in more advanced stages at diagnosis, exhibited more aggressive tumors, and showed poor survival compared to men and postmenopausal women, supporting the role of sex hormones in this pathology. Several reports indicate the estrogen's role in lung carcinogenesis and tumor progression. Thus, there are currently some clinical trials testing the efficacy of antihormonal therapy in lung cancer treatment. This minireview shows the updated data about lung cancer in women, its characteristics, the etiological factors that influence carcinogenesis, and the critical role of estrogen in lung cancer and treatment.